The Innovation Stack : building an Unbeatable Business One Crazy Idea at a Time - McKelvey, Jim, ....- (New York, : Penguin, 2020)
McKelvey's fascinating and humorous stories of Square's early days are blended with historical examples of other world-changing companies built on the Innovation Stack to reveal a pattern of ground-breaking, competition-proof entrepreneurship that is rare but repeatable. The Innovation Stack is a thrilling business narrative that's much bigger than the story of Square. It is an irreverent first-person look inside the world of entrepreneurship, and a call to action for all of us to find the entrepreneur within ourselves and identify and fix unsolved problems--one crazy idea at a time.
Keywords: Innovatie; Ondernemen; Ondernemingen; Veranderingsmanagement